2019
DOI: 10.1111/jocs.13985
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after extracorporeal life support for postcardiotomy cardiogenic shock

Abstract: Background and Aim of the Study Extracorporeal life support (ECLS) may be necessary in refractory postcardiotomy cardiogenic shock (PCS) unresponsive to optimal medical treatment. We sought to analyze the results and temporal outcomes of ECLS for PCS. Methods We performed an observational analysis of our prospective database. In order to analyze the temporal trends of ECLS for PCS, patients were divided into two groups according to the period of ECLS implantation: Group I from January 2007‐June 2012, Group II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The median cardiac arrest duration was 25 minutes (15‐35). Furthermore, CPR duration > 30 minutes was identified as a predictor of in‐hospital mortality, which is in accordance with other studies . The beginning of VA‐ECLS after 30 minutes of conventional CPR is associated with poor survival .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The median cardiac arrest duration was 25 minutes (15‐35). Furthermore, CPR duration > 30 minutes was identified as a predictor of in‐hospital mortality, which is in accordance with other studies . The beginning of VA‐ECLS after 30 minutes of conventional CPR is associated with poor survival .…”
Section: Discussionsupporting
confidence: 90%
“…However, this registry comprises only nonPCS patients. Pozzi et al report 39% in‐hospital survival after VA‐ECLS for PCS in a relatively young cohort of 90 patients (mean age 57.5 ± 15.0 years). Successful weaning from ECLS was accomplished in 45 (50%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of VA ECMO as a bridge to recovery should be considered while discussing elderly surgical candidates at increased risk of post-cardiotomy myocardial failure; the limited number of similar cases in the literature prevents dedicated analyses. 23 Based on patients' baseline profile, the hard question of whether ECMO use is appropriate has to be approached with patients and families before surgery in cases at risk of postoperative myocardial failure. The goal of predicting survival after VV ECMO/VA ECMO support is currently a subject of debate in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nevertheless, the morbidity rate in patients with ECMO is significant, often associated with prolonged hospital stays and poor quality of life for the survivors after hospital discharge. [9][10][11][12][13] Moreover, in-hospital mortality is about 60% 14,15 and 1-year survival is estimated to be 30%. 15 Latest studies showed that patients who have benefited from VA-ECMO for refractory cardiogenic shock after cardiotomy can be weaned off in 48% to 60% of cases.…”
mentioning
confidence: 99%